Quanto option pricing - Prudencio, Rafael Felipe Camargo (2020)
This text aims to explore the quanto options pricing topic, as surprisingly little research has focused on it, despite its relevance. For this purpose, we propose a non-parametric pricing approach and compare it with the pricing of quanto op-tions in a bi-dimensional Heston model framework, proposed by (Dimitroff, et al., 2009), and with the Black-Scholes framework, widely adopted by practitioners. The non-parametric approach aims to be as flexible as possible so that it adapts to a wider range of dependence relations among relevant variables when compared to parametrical models.